(untitled) (Research, Society and Development, 2022)
The present study aims to investigate nursing care for women in prepartum and delivery: focusing on a safe maternity, through the perception of parturientwomen, thus seeking to contribute to the improvement of care, since this, in order to be performed, needs the direct contribution of both professionals and clients. This is a review of narrative literature through bibliographic research and for the construction of this study a search was in the databases of the Virtual Health Library, such as: Latin American and Caribbean Literature on Health Sciences (LILACS) and Scientific Electronic Library Online (SciELO), using the descriptors and their combinations in Portuguese appropriate to the DECS database (Descriptors in Health Sciences): Childbirth, nursing care and Maternal-Infant Nursing. The results highlight the figure of the nurse as a promoter of the safety of women and children at the time of prepartum and delivery, offering her autonomy to choose about the processes to which she will be submitted, being this professional decisive in the biopsychosocial care of women, in addition thinking about how to reduce the risks of injuries during the development of the parturition process. It is up to the nursing professional who assists in labor and delivery, based on a humanistic and holistic model of care, research shows that the committed and qualified nursing professional, who performs normal delivery as a physiological event and adapts dignity, safety and autonomy.